(untitled) (Journal of Global Accounting, 2021)
The study investigates the effect of electronic taxation on revenue generation in Lagos state. Due to tax avoidance and tax evasion that is distorting revenue generation, Lagos state government adopted electronic taxation system. Despite the adoption of electronic taxation, the problem persists. Hence, this study seeks to fill the lacuna and identify how much E- taxation affects revenue generation by examining the effect of E- taxation on revenue generation in Lagos state. Electronic tax payment, Electronic tax filing, Electronic tax clearance Certificate served as proxies to the independent variable Electronic Taxation while Revenue generation is the dependent variable using a sample size of the (40) forty tax stations in Lagos state. The research was carried out using the Ex – post facto research design technique while data were collected from the annual reports of the internally generated revenue at state level which were subsequently analyzed using Linear Regression model and analysis of variance (ANOVA) through the statistical package for social sciences (SPSS 20). The result of the analysis showed that Electronic tax payment, Electronic tax clearance certificate issuance has significant effect on revenue generation in Lagos state while Electronic taxation filing does not significantly affect tax revenue in Lagos state. The result also showed that the interaction of Electronic tax payment, Electronic tax filing and Electronic tax clearance certificate issuance significantly affects revenue generation in Lagos state. The findings concluded that e-taxation has a positive and significant effect on revenue generation in Lagos State. E-taxation provides convenience to taxpayers at a degree that is not available through traditional channels. E-filing also offers the flexibility of time and reduces calculation error on the tax return form to the taxpayers. Therefore, we would conclude that the implementation of e-taxation improves revenue generation in Lagos State. The study recommends that there should be more awareness made on electronic payment channels for taxes, the Lagos State Inland Revenue Service (LIRS) should work out modalities on how to sensitize tax payers on E-tax filing and that more tax clearance certificates should be issued electronically to save time and cost for taxpayers.